Police-community relations in Cincinnati - Ridgeway, Greg, 1973-; Schell, Terry L.; Gifford, Brian; Saunders, Jessica; Turner, Susan, 1954-; Riley, Kevin Jack, 1964-; Dixon, Travis L.; Rand eBooks (Santa Monica, CA : RAND, 2009)
As part of a 2002 collaborative agreement between the Cincinnati Police Department (CPD), the American Civil Liberties Union, and the Fraternal Order of Police, the RAND Corporation annually assesses whether the parties are achieving their goals of improving police-community relations in Cincinnati. Specifically, the parties aim to ensure that police officers and community members become proactive partners in community problem-solving; build relationships of respect, cooperation, and trust within and between police and communities; improve education, oversight, monitoring, hiring practices, and accountability of CPD; ensure fair, equitable, and courteous treatment for all; and create methods to establish the public's understanding of police policies and procedures and recognition of exceptional service in an effort to foster support for the police. This fourth report analyzes a follow-up wave of surveys of the community, officers, and those involved in the complaint processes; reviews statistical compilations, motor-vehicle stops, and videotaped citizen-police interactions; and contains the final assessment of the progress toward the goals of the collaborative agreement. The authors conclude that CPD is not the same as the department that policed Cincinnati in 2001. Policy changes, oversight, and a variety of reforms have produced a department that polices differently than it had in 2001. The authors report reduced crime, small but positive changes in the community's perception of the department, and no evidence of racial bias in traffic stops. While the trends appear positive, without a concerted effort to ameliorate the disparate impact of these policies, it seems likely that black Cincinnati residents will remain less satisfied with policing services than will their white counterparts.
Introduction -- The context of policing in Cincinnati: crime, arrests, and use of force -- Analysis of vehicle stops -- Analysis of videotaped police-motorist interactions -- Police-community satisfaction survey -- Satisfaction of police officers working in Cincinnati -- Citizen and officer satisfaction with the complaint process -- Summary and conclusions -- Appendix A: Police-community satisfaction survey instrument -- Appendix B: Police officer survey instrument -- Appendix C: Complaint survey instruments -- Appendix D: Summary of community-police satisfaction survey -- Appendix E: Details of propensity-score weighting -- Appendix F: Estimating false-discovery rates -- Appendix G: RAND-Cincinnati Police Department year 4 2007 police-civilian videotaped interactions codebook -- Appendix H: Cincinnati Police Department's response to year 4 report -- Appendix I: American civil liberties union response to year 4 report.
"A RAND Infrastructure, Safety, and Environment."
"RAND Safety and Justice."
"This research was conducted under the auspices of the RAND Center on Quality Policing within the Safety and Justice Program of RAND Infrastructure, Safety, and Environment (ISE)"--Pg. IV.
Includes bibliographical references (p. 251-255).
Also available on the internet via WWW in PDF format.
Keywords: Community policing -- Cincinnati (Ohio); Police -- Cincinnati (Ohio) -- Public opinion; Police-community relations -- Cincinnati (Ohio); Social surveys -- Cincinnati (Ohio); Electronic books